Integrated Teaching Strategies Used by ESL Teachers: How are Strategies of Arts, Mathematics, and Sciences Correlated? - Mingchu Neal Luo (The Advocate, 2019)
The emerging popularity of interdisciplinary teaching stems from research-based student gains in learning. Using the interdisciplinary and integrated framework of STEAM, this study aims to understand ESL teachers’ integrated teaching strategies of arts, mathematics, and sciences, and examine the correlation among the domains of linguistic, artistic, musical, mathematical and logical, and science-related teaching strategies. Data collected from 67 ESL teachers in a Midwestern state was analyzed using the Pearson correlations. Results indicated that ESL teachers not only emphasize the traditional linguistic teaching strategies, but also integrate artistic, musical and mathematical, and sciences-related strategies in their classroom teaching. ESL teachers’ classroom teaching strategies of arts, mathematics, and sciences were both moderately and highly correlated. Interpretations of the findings related to the integrated perspective of interdisciplinary teaching and implications for both teacher educators and school administrators were discussed.
Keywords: interdisciplinary teaching; ESL teacher; integrated teaching strategy; correlation